The necessity and ways of realization of industrial and innovative development of agro-industrial complex to ensure food security in Kazakhstan (Journal of Economic Research & Business Administration, 2015)
In this article the author considered problem of food security in Kazakhstan. Also is offered system analysis of food security in Kazakhstan by comparing the share of imports in the trade balance and the share of domestic food processing. In conclusion the author offered ways of solving the food problem in industrial and innovative development of agriculture of Kazakhstan.
Keywords: food security; foodstuffs import; agricultural products; home produced foodstuffs; agricultural complex of Kazakhstan; industrial and innovative development of agriculture.